2020
DOI: 10.15171/jlms.2020.05
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Adding Electromagnetic Therapy or Laser Therapy to Medications in Patients With Diabetic Peripheral Neuropathy

Abstract: Introduction: Diabetes mellitus (DM) is a common disease with a highly significant burden among the Saudi population. This study aimed to investigate the effects of adding either magnetic or laser therapy to medications in patients with diabetic peripheral neuropathy (DPN). Methods: Seventy-one medically controlled diabetic patients were randomly assigned to 1) Magnetic group: 26 patients were exposed to magnetic therapy for 20 minutes/session, 2 sessions/week, for 3 months 2) Laser group: 25 patients were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
(112 reference statements)
0
8
0
1
Order By: Relevance
“…Fifteen studies were declared eligible and approved by the authors and two co-authors. However, two studies are not applicable using CASP (Shanb et al, 2020;Win, Fukai, Nyunt, & Linn, 2020).…”
Section: Assessment Of Study Feasibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies were declared eligible and approved by the authors and two co-authors. However, two studies are not applicable using CASP (Shanb et al, 2020;Win, Fukai, Nyunt, & Linn, 2020).…”
Section: Assessment Of Study Feasibilitymentioning
confidence: 99%
“…Four studies demonstrated the longest duration of the intervention: undergoing a combination of resistance-aerobic training for 16 consecutive weeks (Parsa, Hosseini, Bije, & Nia, 2018), following a low-fat plant-based diet for 20 weeks (Bunner et al, 2015); and undergoing 2 mL topical Citrullus colocynthis therapy for 36 weeks (Heydari, Homayouni, Hashempur, & Shams, 2016). Magnetic therapy was administered for 20 minutes/session for 36 weeks (Shanb et al, 2020) and underwent foot reflexology therapy 30 minutes/day for 48 weeks (Ibrahim & Rizk, 2018).…”
Section: Application Technique and Duration Of Cam In Dn Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Today it is difficult to find a disease in the treatment of which one or another type of magnetotherapy could not be used. Softness of exposure, wide possibilities for personalization and accessibility of the method made magnetotherapy a popular type of treatment and prevention [15][16][17][18].…”
Section: Magnetic Coronavirus Therapymentioning
confidence: 99%
“…Electromagnetic fields also have analgesic, anti-inflammatory, anti-swelling action and cause vasodilation. They are considered a safe complementary treatment for patients with DPN, however, their application is more limited [10] . The aim of this review is to present research data on the aforementioned electrotherapy tools and their results in the treatment of pain in patients with DPN.…”
Section: Introductionmentioning
confidence: 99%